Особливості формування маркетингових стратегій підприємств ресторанного бізнесу - Шквиря, Наталя Олександрівна; Кукіна, Наталя Володимирівна; Shkvyria, Natalia; Kukina, Natalia (Запоріжжя : Видавничий дім «Гельветика», 2024)
UA: У статті проаналізовано особливості формування маркетингових стратегій підприємств ресторанного бізнесу. Визначено основні компоненти маркетингової стратегії підприємств ресторанного бізнесу. Розглянуто інструменти цифрового маркетингу підприємств ресторанного бізнесу. Систематизовано ефективні маркетингові стратегії, що застосовуються у ресторанному бізнесі для залучення та утримання клієнтів. /// EN: The article analyzes the features of the formation of marketing strategies of restaurant business enterprises. The need to develop a marketing strategy for restaurant business enterprises is substantiated: optimization of the internal activities of the enterprise, which is the basis for attracting investors and partners. Taking into account the specifics of restaurant services, the components of the marketing strategy were specified, namely: determining the potential group of customers, ways to establish contacts, the required quality of services, pricing policy and marketing communications. It is argued that the diversity of operating conditions for restaurant business enterprises in Ukraine requires a differentiated approach to the use of marketing in determining their development strategies. It was determined that the most acceptable and stable strategy for Ukrainian restaurant businesses in terms of achieving strategic success is a differentiated marketing strategy, the development of which should take into account a number of factors, namely: high quality of products and ingredients used in the preparation of culinary products; the possibility of providing discounts, bonuses, low prices; providing customers with a wide range of dishes; convenient location of restaurant businesses; high quality of service; provision of additional services; the possibility of exclusive customer service; an interesting and competent description of the composition and features of dishes on the menu. Research has shown that successful customer acquisition and retention in the restaurant business requires comprehensive marketing strategies that include a deep understanding of the target audience and precise positioning. The practical implementation of these strategies requires a systematic approach, including analysis and adaptation of marketing tools depending on the specifics of each establishment. Digital marketing plays an important role, allowing you to expand your audience reach and manage your reputation in the online space.
Features of formation of marketing strategies for restaurant business
Keywords: маркетинг; маркетингова стратегія; сегментування ринку; підприємство ресторанного бізнесу; інструменти цифрового маркетингу; marketing; marketing strategy; market segmentation; restaurant business; digital marketing tools